2004
DOI: 10.1063/1.1664208
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Transparency in Exclusive ρ0 Production at HERMES

Abstract: Exclusive coherent and incoherent electroproduction of the p° meson from 1 H and 14 N targets has been studied at the HERMES experiment as a function of coherence length (l c), corresponding to the lifetime of hadronic fluctuations of the virtual photon, and squared fourmomentum of the virtual photon (-<2 2). The ratio of I4 N to *H cross sections per nucleon, called nuclear transparency, was found to increase (decrease) with increasing coherence length for coherent (incoherent) p° electroproduction. For fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…This makes the c.m.-energy available for the Θ + (1530) to be smaller than for the Λ(1520) . Similar evidence may come also from preliminary data of the HERMES Collaboration [65]. When the standard kinematic constraints, used for the Θ + -observation, are appended by the requirement of an additional detected pion, the signal/background ratio essentially improves.…”
Section: Positive Datasupporting
confidence: 50%
“…This makes the c.m.-energy available for the Θ + (1530) to be smaller than for the Λ(1520) . Similar evidence may come also from preliminary data of the HERMES Collaboration [65]. When the standard kinematic constraints, used for the Θ + -observation, are appended by the requirement of an additional detected pion, the signal/background ratio essentially improves.…”
Section: Positive Datasupporting
confidence: 50%
“…The experimental findings were reported in real [1,2,3,4] and quasi-real photoproduction experiments [5], and further positive sightings were reported in K-nucleus collisions [6], pp [7] and pA [8,9] reactions, and in neutrino [10,11] and deep inelastic electron scattering [12], for a total of around a dozen positive results. Currently only the charge and strangeness of this state, which has been labeled Θ + , are known; its spin, parity and isospin are as yet undetermined, although there are hints [13] that it may be isospin zero. The mass of the Θ + is found to be around M Θ + = 1540 MeV.…”
Section: A Phenomenologymentioning
confidence: 99%
“…However, these experiments have been criticized 13 because they cannot determine the strangeness in the K 0 p final state. In this workshop, the HERMES collaboration 14 showed that the K 0 p peak in their results is not consistent with an interpretation as a Σ * + resonance. They also showed that the peak to background ratio in their data can be enhanced by applying cuts that remove the known K * and Λ * resonances.…”
Section: Reasons To Be Optimisticmentioning
confidence: 99%